Effects of heavy metals on male gametes of sweet cherry. Issue 2 (3rd April 2017) - Sharafi, Yavar; Talebi, Seyyedeh Farhnaz; Talei, Daryush
Abstract: Fruit set is affected by different environmental, biological, physical and chemical factors. Abnormal conditions in pollination, fertilization and fruit set period can reduce orchard yield. Sweet cherry is one of the most important stone fruits of Iran which was ranked third with 200, 000 tons in 2012 in the world by an FAO report. Pollen germination and tube growth are the major factors of fruit set in sweet cherry. In polluted cities, this phenomenon may be affected by heavy metals stresses. In this study, the effects of different concentrations of heavy metals – cadmium, lead, copper and mercury by 0 (control), 50, 100, 150, 200 and 250 ppm) – were studied on pollen germination and tube growth of 10 sweet cherry cultivars in vitro . The results demonstrated that both traits were significantly affected by different levels of heavy metals, cultivars and interaction among them. Pollen germination and tube growth of all cultivars were reduced with increase in metals concentrations. In the concentration of 250 ppm of all heavy metals, pollen germination and tube growth was close to 0 in most cultivars. Cadmium showed the highest toxicity on pollen germination and tube growth and among the cultivars, "Zard-eDaneshkadeh" exhibited highest sensitivity, while "Colt" demonstrated highest tolerance to stress from the studied metals.